Pushing the limits of wheelchair technology for paralympics - Tan, Zachary Jek Ming (2016)
This report seeks to cover the detailed product development process of developing modular wheelchair components specifically for the para table tennis athletes in the Class 1 and 2 categories. It covers the chronological project process, from the market research to the fabrication of the prototype which would then be tested and utilized by the athletes during the ASEAN Para Games 2015. The process started with the user and task analysis, whereby the para athletes underwent several tests to determine their physical and cognitive capabilities regarding reach, reaction timing and tipping angle; with the aid of measurements acquired from the tests. From the results and further interviews conducted, their physical difficulties and limitations were pinpointed and thus begun the product design process to improve on those areas with the goal of maximising their capabilities. The designs of the components were developed while adhering strictly to the user’s needs and feedback. The final designs were subjected to tests such as the finite element analysis to justify its ability in withstanding the calculated amount of forces and stresses. These external forces would be exerted via the typical movements from the athlete whilst undergoing a typical match. With the fabrication completion of the prototype, they were being tested by the para athletes who underwent the same test from the task analysis. The measurements from both tests were then analysed and compared to determine if the newly designed components have a significant improvement regarding the athletes’ performance, and this would thus increase their title hopes in the ASEAN Para Games 2015.